Brain–Gut–Microbe Communication in Health and Disease - Grenham, Sue; Clarke, Gerard; Cryan, John F.; Dinan, Timothy G. (Frontiers in Physiology, 2011)
Bidirectional signalling between the gastrointestinal tract and the brain is regulated at neural, hormonal and immunological levels. This construct is known as the brain-gut axis and is vital for maintaining homeostasis. Bacterial colonisation of the intestine plays a major role in the post-natal development and maturation of the immune and endocrine systems. These processes are key factors underpinning central nervous system (CNS) signalling. Recent research advances have seen a tremendous improvement in our understanding of the scale, diversity and importance of the gut microbiome. This has been reflected in the form of a revised nomenclature to the more inclusive brain-gut-enteric microbiota axis and a sustained research effort to establish how communication along this axis contributes to both normal and pathological conditions. In this review, we will briefly discuss the critical components of this axis and the methodological challenges that have been presented in attempts to define what constitutes a normal microbiota and chart its temporal development. Emphasis is placed on the new research narrative that confirms the critical influence of the microbiota on mood and behaviour. Mechanistic insights are provided with examples of both neural and humoral routes through which these effects can be mediated. The evidence supporting a role for the enteric flora in brain-gut axis disorders is explored with the spotlight on the clinical relevance for irritable bowel syndrome (IBS), a stress-related functional gastrointestinal disorder. We also critically evaluate the therapeutic opportunities arising from this research and consider in particular whether targeting the microbiome might represent a valid strategy for the management of CNS disorders and ponder the pitfalls inherent in such an approach. Despite the considerable challenges that lie ahead, this is an exciting area of research and one that is destined to remain the centre of focus for some time to come.